The Components of the Circular Velocity of Money - Angell, James W. (Quarterly Journal of Economics, 1937)
I. Introduction: the basic equation, 224. — II. Production one batch at a time; the length of the "production process" as the determinant of circular velocity, 226. — III. Production in overlapping batches; the intervals between successive payments; the relative timing of payment schedules; other determining factors, 230. — IV. Several different production processes; shifts in demand; new investment, 243. — V. "Idle" balances of cash; their effect on circular velocity; probably the chief source of short-period fluctuations in velocity, 251. — VI. The statistical data; inferences therefrom, 259. — VII. The related problem of working capital. Three definitions; the value of working capital, 264.